Implementasi Strategi Pemasaran Produk Dalam Meningkatkan Volume Penjualan Produk UMKM Di Dusun Hatusua Kabupaten Seram Bagian Barat - Huwae, Victor Ernest; Latuconsina, Zainuddin; Siahainenia, Silfiena (Community Engagement and Emergence Journal (CEEJ), 2024)
The purpose of this training is to provide MSME actors with a better understanding and skills of effective marketing strategies. This training aims to address the problems faced by local MSMEs, such as increasingly fierce competition, limited market access, and lack of knowledge about digital marketing. For these activities, participatory approaches, problem-based training and hands-on demonstrations are used. This training teaches participants basic marketing concepts such as market segmentation, branding, digital promotion, and the use of social media and marketplaces to increase market reach. The training also teaches them the technical skills to create engaging promotional content and use digital analytics tools to track the success of marketing campaigns. The results of the activity showed that participants understood contemporary marketing strategies better. MSME marketers are starting to use digital marketing through e-commerce platforms and social media. This results in an increase in product sales. In addition, this program has succeeded in encouraging the formation of a local business cooperation network and has a positive impact on the economy of Hatusua Hamlet.